Institutional change for museums : a practical guide to creating polyvocal spaces - Pegno, Marianna; Souffrant, Kantara (Abingdon, Oxon ; New York : Routledge, 2024)
"Institutional Change for Museums: A Practical Guide to Creating Polyvocal Spaces demonstrates how museums can enact institutional change by implementing systematic and structural approaches to anti-racist, anti-colonial, and anti-elitist practices. This practical guide brings together museum and heritage experts, artists, organizers, and cultural workers to present thoughtful, polyvocal critiques and solutions for conceptualizing museums of the future. These authors embrace hybrid identities, complicate concepts of nationalism, straddle disciplines, and extend the concept, function, and literal place and definition of the "museum." The book shows that museums must cultivate practices that center people, interrogate colonial legacies, take new approaches to curatorial ethics and caring for objects, and imagine new strategies for asserting the relevance of museums, to create institutional change. This resource challenges traditional approaches to museology by offering scholarly research and case studies alongside personal narratives and speculative fiction. Institutional Change for Museums will be an invaluable resource for museum professionals and cultural workers, including curators, educators, and researchers. It will also be beneficial to those studying or researching in Museum and Heritage Studies, Cultural Studies, Feminist Studies, Visual Culture, Social Justice, and Postcolonial Studies"--
Keywords: Museums -- Management; Organizational change